Evolution of price policy for offshore wind energy in China: Trilemma of capacity, price and subsidy. (February 2021) - Wei, Youzhou; Zou, Qing-Ping; Lin, Xianghong
Abstract: China promotes the development of the offshore wind industry to reduce CO2 emissions, tackle air pollution, commit to the Paris Climate Agreement and develop a strategic emerging industry. The installed capacity of offshore wind power in China reached 4445 MW in 2018 which was ranked third in the world. Big developers dominated the offshore wind energy market with domestic turbines. Many projects are under construction. The offshore wind industry in China has experienced four stages of price policy: demonstration, concession, feed-in tariff and market-oriented competition policy. Nevertheless, it is impossible to expand the installed capacity, lower the on-grid price (cost) and reduce the subsidy for the offshore wind power industry at the same time. This is the trilemma (impossible trinity) that needs to be addressed by the price policy. In the past decade, China has implemented an evolving price policy, i.e., a system and mechanism that encourage firms to invest in the offshore wind industry to expand the capacity of the industry by setting price and providing subsidy and other benefits. An overall evaluation based on the indicators of installed capacity, price, subsidy, spatial distribution, technology and industrial linkage shows that the price policy has been effective in balancing capacity, price and subsidy up to now. However, lowering the price and reducing the subsidy will be the major challenges that China has to overcome in the coming years in order to sustain its current growth trend. To boost the development of its offshore wind industry further, China needs to implement a market-oriented competition price policy and mechanism, learn from the experience of price policy evolution in European countries and open the market to foreign investors. Highlights: The offshore wind industry of China has achieved a great leap forward in the past decade. Addressing the trilemma capacity, price and subsidyis more critical for the offshore wind industry in China than for European countries. Evolution of price policy for offshore wind demonstrates the flexibility and resilience of Chinese policy. The price policy success is indicated by capacity, price, subsidy, spatial distribution, technology and industrial linkage. Lowering the price and reducing the subsidy should be the priorities of the new price policy.